2010
DOI: 10.1016/j.jcf.2010.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Mutational spectrum of cystic fibrosis in the Lebanese population

Abstract: The most common CFTR mutations in addition to five mutations not previously described in the Lebanese population were identified. Identification of CFTR mutations in the Lebanese population is important for molecular investigations and genetic counseling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(52 citation statements)
references
References 28 publications
2
50
0
Order By: Relevance
“…Moreover, consanguinity is still on the rise and is associated with a high frequency of genetic diseases among Arabs . Similarly, consanguinity was found to be high among CF patients in several Arab countries, for example, in 50% of CF patients in Lebanon, 50% in Egypt and Algeria and 54.3% in Kuwait . In Qatar, the consanguinity rate is reportedly approximately 98% among 26 related Arab Bedouin families with CF, 88% in Saudi Arabia and 77% in Bahrain .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, consanguinity is still on the rise and is associated with a high frequency of genetic diseases among Arabs . Similarly, consanguinity was found to be high among CF patients in several Arab countries, for example, in 50% of CF patients in Lebanon, 50% in Egypt and Algeria and 54.3% in Kuwait . In Qatar, the consanguinity rate is reportedly approximately 98% among 26 related Arab Bedouin families with CF, 88% in Saudi Arabia and 77% in Bahrain .…”
Section: Resultsmentioning
confidence: 99%
“…Likewise the Àa 4.2 single gene deletion which is commonly reported in Arab countries was absent in our population [2,15,30]. A possible explanation to the disparity between our results and those reported from other Arab studies may be due to the heterogeneous backgrounds of our families in contrast to the more pure Arab homogenous background [34].…”
Section: Resultsmentioning
confidence: 99%
“…However, the highest frequency is reported from a Middle Eastern study in 2010. Farra et al revealed its occurrence to be 27% in Lebanon. As a result, many countries included this mutation to their neonatal screening programs.…”
Section: Discussionmentioning
confidence: 99%